Information technology governance and higher education in Malaysia: practices and impacts - Ajayi, Binyamin Adeniyi; Hussin, Husnayati (IIUM Press, International Islamic University Malaysia, 2017)
Information Technology Governance (ITG) is the deliberate behaviour adopted by senior management in the corporate design of Information Technology (IT) and for enterprise use to enable continuous organisation performance. Research in recent times has been reporting issues on ITG phenomenon in the organisation. However, studies on educational institutions, especially in developing nations, are scarce despite the increase in recognition of the importance of ITG. Moreover, few embed theoretical underpinnings to extend knowledge. This study, based on organisation learning and contingency theories, explores how universities achieve performance through designed ITG. It examines antecedents of ITG absorptive capacity and its influence on performance in the context of developing nations’ universities. Using a sequential mixed method research design, it carries out an exploratory and correlational study. It avails itself to documents, websites and interview sessions with executive and senior managers, in a phenomenological case study on International Islamic University Malaysia. It applies the thematic coding style to generate themes relative to analysed documents. The themes and knowledge from past studies informed the design of the questionnaire. It administers the questionnaire purposively and randomly on strata of business and IT functions senior level managers drawn from seven public and three private universities in Malaysia. Subjecting the data to Exploratory Factor Analysis (EFA), a scale of 44 items, content valid and reliable, was found to be parsimonious enough in explaining seven dimensions of the three variable ITG model, consisting of: ITG mechanism, ITG absorptive capacity and organisation ITG performance. Using the Multiple Regression Analysis (MRA) techniques on these three variables reveals the mediating effect of ITG absorptive capacity. ITG absorptive capacity fully mediates, and better explains the effect of ITG mechanism on organisation ITG performance. The resultant model, as well as the multiple-item scale, can be adapted in future to study the systemic role of ITG on organisation performance. This study suggests that proper ITG behaviour results in enhanced business and IT knowledge, which in turn influences organisation’s ability to perform. The report identifies some implications of the study and future directions.